Foliar nitrogen application for enhancing growth, productivity and nitrogen use efficiency in sunflower (Helianthus annuus) - SARVARI, B A; SINGH, V K; SHEKHAWAT, KAPILA; OBAID, H; WASIFHY, M K; BARAKZAY, K R; RATHORE, S S (The Indian Journal of Agricultural Sciences, 2020)
Sunflower (Helianthus annuus L.) is a promising oilseed crop of Afghanistan mainly grown under resource constraint situations. The poor nitrogen status of the soil makes nitrogen deficient for plants at the sensitive stages resulting in severe growth and yield decline. The present study compared the effect of nitrogen application as basal vis-Ã -vis in combination with foliar application at different crop growth stages on growth, productivity and nutrient use efficiency in sunflower. The application of 50 kg N/ha as basal along with two 1.5% foliar spray of N at 20 and 40 DAS resulted in higher growth parameters, yield and nutrient use efficiency in sunflower. Nitrogen application applied as basal met out the initial nitrogen demand and when supplemented with foliar application resulted in higher assimilating surface area, dry matter accumulation and higher yield attributes and yield in sunflower.